2012
DOI: 10.1021/cn300077c
|View full text |Cite
|
Sign up to set email alerts
|

Role of ABC Transporters in the Pathogenesis of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the most common form of age-related dementia that begins with memory loss and progresses to include severe cognitive impairment. A major pathological hallmark of AD is the accumulation of beta amyloid peptide (Aβ) in senile plaques in the brain of AD patients. The exact mechanism by which AD takes place remains unknown. However, an increasing number of studies suggests that ATP-binding cassette (ABC) transporters, which are localized on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 150 publications
1
88
0
2
Order By: Relevance
“…As a peptide, Ab 40 has poor passive membrane permeability and depends on a transport system to pass through endothelial cells of the blood-brain barrier (BBB) (Banks et al, 2003). Low-density lipoprotein receptor-related protein-1 (LRP1) is the major receptor that mediates removal of Ab across the BBB in its free form (Deane et al, 2004) or bound to chaperone molecules such as apolipoprotein E. P-glycoprotein (P-gp), expressed on the luminal side of the BBB, mediates the efflux of Ab into the peripheral circulation (Cirrito et al, 2005;Abuznait and Kaddoumi, 2012). It has been reported that the expression of LRP1 and P-gp at the BBB is decreased and expression of the receptor of advanced glycation end product (RAGE), which influxes circulating Ab into the brain across the BBB, is increased in AD patients, which favors Ab accumulation inside the brain (Deane et al, 2003Donahue et al, 2006;Sagare et al, 2007;Castellano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As a peptide, Ab 40 has poor passive membrane permeability and depends on a transport system to pass through endothelial cells of the blood-brain barrier (BBB) (Banks et al, 2003). Low-density lipoprotein receptor-related protein-1 (LRP1) is the major receptor that mediates removal of Ab across the BBB in its free form (Deane et al, 2004) or bound to chaperone molecules such as apolipoprotein E. P-glycoprotein (P-gp), expressed on the luminal side of the BBB, mediates the efflux of Ab into the peripheral circulation (Cirrito et al, 2005;Abuznait and Kaddoumi, 2012). It has been reported that the expression of LRP1 and P-gp at the BBB is decreased and expression of the receptor of advanced glycation end product (RAGE), which influxes circulating Ab into the brain across the BBB, is increased in AD patients, which favors Ab accumulation inside the brain (Deane et al, 2003Donahue et al, 2006;Sagare et al, 2007;Castellano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A folyamat kiváltója ismeretlen, de az utóbbi évek kutatásai az ABC-transzporter fehérjék szerepére is fényt derítettek. Így elsősorben a P-gp-, BCRP-, MRP1-és koleszteroltranszporter fehérjék összefüggéseit mutatták ki az Alzheimer-kór patológiájával, illetve a béta-amiloid plakkok lerakódásával kapcsolatban [53]. Lam és mtsai bizonyították az Aβ 40 és Aβ 42 P-gp szubsztráttulajdonsá-gát [54].…”
Section: Alzheimer-kórunclassified
“…In addition to altering pharmacokinetics and pharmacodynamics, BCRP polymorphisms are associated with disease states such as Alzheimer's disease and gout (Matsuo et al, 2011b;Feher et al, 2013;Takada et al, 2014). The association between BCRP and these disease states is hypothesized to be secondary to BCRP dependent handling of amyloid beta in Alzheimer's disease and uric acid in patients with gout (Matsuo et al, 2011a,b;Abuznait and Kaddoumi, 2012).…”
Section: B Atp Binding-cassette Drug Transportersmentioning
confidence: 99%